2015
DOI: 10.1039/c5nr03047a
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastable conjugate of silver nanoparticles and protein formed through weak interactions

Abstract: In recent years, silver nanoparticles (AgNPs) have attracted significant attention owing to their unique physicochemical, optical, conductive and antimicrobial properties. One of the properties of AgNPs which is crucial for all applications is their stability. In the present study we unravel a mechanism through which silver nanoparticles are rendered ultrastable in an aqueous solution in complex with the protein ubiquitin (Ubq). This involves a dynamic and reversible association and dissociation of ubiquitin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 58 publications
(120 reference statements)
0
34
0
Order By: Relevance
“…25 Moreover, the ubiquitin surface is similar to what was identified in earlier studies of ubiquitin-surface interactions. 4346 Each cluster of ionizable residues experiences different p K a values depending on whether the protein is adsorbed on the AuNP surface or exposed to solution (Figure 3A). For simplicity, model-compound p K a values are used for the solution state, and each residue type is assigned an identical p K a shift.…”
Section: Resultsmentioning
confidence: 99%
“…25 Moreover, the ubiquitin surface is similar to what was identified in earlier studies of ubiquitin-surface interactions. 4346 Each cluster of ionizable residues experiences different p K a values depending on whether the protein is adsorbed on the AuNP surface or exposed to solution (Figure 3A). For simplicity, model-compound p K a values are used for the solution state, and each residue type is assigned an identical p K a shift.…”
Section: Resultsmentioning
confidence: 99%
“…Brahmkhatri et al . demonstrated that a conjugate of AgNP with Ubq is highly stable over a wide range of pH values compared to the bare AgNP . Chemical shift perturbation was used to identify the Ubq residues responsible for binding with AgNP and the NMR titrations were carried out to measure the dissociation constant ( K D ) .…”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…Generally, silver nanoparticles appear to have weaker protein binding compared to AuNPs, and AgNPs can gradually undergo oxidative dissolution in biological fluids, eventually dissolving while releasing soluble Ag + ions . This reduced stability appears to influence protein binding, leading to a more dynamic corona when observed by NMR …”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…Finally, the products were kept in a desiccator over silica gel. The physical and spectral data (IR and UV visible) of the compounds are collected in Tables 1 and 2 3.67(bs, 4H j,j' ), 2.87(bs, 6H h,h',i.i' ), 2.73(bs, 4H g,g' ) ppm. 13 C NMR (in DMSO): 167.32(C 7,7 0 ), 145.22(C 5,5 0 ), 135.05(C 4,4 0 ), 129.93(C 1,1 0 ), 128.86(C 2,2 0 ), 127.61(C 3,3 0), 126.39(C 6,6 0 ), 57.02(C 10,10 0), 48.05 (C 8,8 0), 46.02(C 9,9 0 ) ppm.…”
Section: Synthesis Of Cadmium Complexesmentioning
confidence: 99%
“…Antibacterial, antiviral, anti-flammatory, anti-oxidant activities, antifungal, analgesic and anti-tubercular are some notable properties of Schiff base complexes in biological field although they have extensive usage in other scientific fields. [1][2][3][4][5][6] In medical chemistry field, Schiff base complexes are known as new anti-cancer agent because of their abilities in cleavage of DNA strands and destruction of cancer cell. [7,8] Among many works on the Schiff base complexes, recently various researches on the cadmium Schiff base complexes and their applications have been reported.…”
Section: Introductionmentioning
confidence: 99%